Pengaruh Cognitive Behavior Therapy Terhadap Post Traumatic Stress Disorder Pada Anak Korban Kekerasan Seksual : Literature Review - Reliani Reliani; Septian Galuh Winata (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To determine the effect of cognitive behavior therapy on post-traumatic stress disorder in child victims of sexual violence. Methods: Literature review of the journal cognitive behavior therapy on post-traumatic stress disorder in child victims of sexual violence. Internet search for articles with data- bases: PubMed-NIH, NCBI-PMC, and Google Schoolar. The review was carried out by 10 articles starting in 2010-2020, using English and Indonesian, types of research journal articles, full text availability, Medline journal category. Keywords: Cognitive behavioral therapy, Post-traumatic stress disorder, Child sexual abuse. Results: In the Literature review, the researchers found that in 10 articles studied, all of the articles mentioned Cognitive behavioral therapy (CBT) is an alternative therapy and psychoeducation that is effective in reducing the level of risk of psychological prob- lems in children, the majority in the articles are girls with PTSD on sexual violence problems. The CBT therapy process is carried out in several sessions, namely 12 to 16 sessions, post-test monitoring is carried out after the intervention is carried out at the earliest 12 weeks to 6 months to assess the success of CBT psychoeducation. Conclusion: Cognitive behavioral therapy (CBT) can be an alternative method of psy- choeducational therapy in children with the same problem to reduce the worsening of the psychological prognosis in children.